OPTIMASI WAKTU DAN BIAYA PELAKSANAAN PROYEK JALAN DENGAN METODE CRASH PROGRAM (STUDI KASUS PEMELIHARAAN JALAN KECAMATAN TENGGARONG SEBERANG DAN TENGGARONG) - Bernardo Sandrini Salasa Sandrini Salas; Dharwati P. Sari; Anung Sudibyo; Achmad R. Nur (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Time, cost, and quality are three important elements of schedule that should be made in detail in order to assist in the evaluation of the project. In this research, we analyzed the acceleration of project completion duration. The case study on this research was taken in Tenggarong Seberang District and Tenggarong District. The method used in this research is the crash program method with the alternative implementation with a variety of added work hours and manpower, which are adding 1 hour, 2 hours, and 3 hours of work hours also the alternative of adding 25% and 50% of the manpower. This research aimed to determine the total time and cost of implementing the project after the crashed and determined the results of an optimal acceleration alternative by comparing the results of the analysis of the application of the crash program method. The work was accelerated (crashed) in this research is work that is on the critical path. The results of the application of the crash program method with the addition of working hours and manpower obtained an efficient acceleration alternative, namely the addition of 3 hours of working hours which resulted in the acceleration duration being 67 days or 25.56% faster than the normal duration of 90 days with a total acceleration cost of Rp 1,213,717,588.81 or 0.213% lower than the normal total cost of Rp 1,216,303,515.90.